Economists and Minimum Wage Laws - Jirásek, Tomáš; Šťastný, Dan, 1974-; Koubek, Ivo, 1959-; Vysoká škola ekonomická v Praze. Národohospodářská fakulta (2012)
The minimum wage is a tool of public policy which despite being in favor of politics tends to be in displeasure of economists. Recent consensus study shows (Alston, 1992; Fuller, 2003) that consensus on minimum wage among economists has a tendency for weakening. The goal of my thesis was to map the consensus of economists on minimum wage in the course of the 20th century and to help to answer the question how the view of economists has changed on this topic and which events were of greatest influence. As a way of measuring the consensus I chose the studying of academic articles because it is the direct output of academic community. My study shows that from the 1930s we can see a constant strengthening of ideas that a minimum wage has a negative effect on economy.
Vedoucí práce: Daniel Šťastný
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Národohospodářská fakulta, 2013
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2013
Způsob přístupu: Internet
Keywords: ekonomická analýza [obor dipl. práce]; diplomové práce; master's theses